TEKNOLOGI ROBOT - Pashori, Aswar; Iswadi, Iswadi (Universitas Islam Negeri Alauddin Makassar, 2014)
Living in 21st century is living with higher technology. Technologies are use in daily live from basic needed to secunder or tersier needed. One of the most popular and advantage technology is robot. Robot can help many kinds of job or anything that people need, from industry, manufacturing, disaster, terrorism or astronot robot. This paper shows that all about robot such as definition, classification, function, programming systems and future research of robot